Strength properties of finger jointed wood from fast growing species / M Rafais M Razip, Wan Mohd Nazri Wan Abdul Rahman and Jamaludin Kasim - M Razip, M Rafais; Wan Abdul Rahman, Wan Mohd Nazri; Kasim, Jamaludin (2012)
Finger jointing short pieces of lumber has become an increasingly popular method of reducing wood waste and utilizing shorts to realize maximum profit from the steadily rising cost of raw materials. This study was conducted to evaluate the mechanical properties of finger joint from Hevea brasiliensis and Leucaena spp. at three portion (top.middle.bottom), and to determine the effect of species on jointing system. Polyvinyl acetate (PVAc) was used to joint these specimen. This two species and the combination were tested in verticle orientation for bending properties (modulus of elasticity and modulus of rupture) conforming to the European standard (EN 408:2003). The result revealed that the tests specimen from the two species and the combination was strong enough for use as material in furniture making. Thus, it can be concluded that finger joint from Hevea brasiliensis and Leucaena spp. can successfully be produced as the main source of raw materials for finger joint.